2016
DOI: 10.9775/kvfd.2016.15145
|View full text |Cite
|
Sign up to set email alerts
|

Ratlarda Deneysel Siklofosfamid Toksikasyonunda Silimarin ve Curcuminin Koruyucu ve Antigenotoksik Etkileri

Abstract: The aim of this study was to investigate the protective effects of silymarin (SLY) and curcumin (CUR), which have strong antioxidant properties, against the toxic effects of high dose of cyclophosphamide (CP) on the liver and kidneys of rats. For this purpose, a total of 36 adult Wistar albino female rats at the weight of, 250±10 g were used. Biochemical parameters were found to be significantly higher in the CP-only group than in the other groups. In the groups in which SLY and CUR were administered concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While pleomorphic nuclei (indicated by the yellow arrow) and focal necrosis (indicated by the black arrow) are observed in the heart muscle of the rats administered CPx + 5 mg/kg kefir (Figure 8d), a focal hyalinization area (indicated by the gray arrow) is observed in the heart muscle of the rats administered CPx + 10 mg/kg kefir (Figure 8f). Also, studies have shown that in the cardiac tissue of experimental groups given CPx, there are changes in the staining properties of the cell cytoplasm, a darker color and shrinkage in the nuclei, bleeding between muscle cells, small inflammatory cell foci and the separation of muscle fibers [12,25]. The histological findings of the experimental study conducted by Motawi et al (2010) involving the administration of 200 mg/kg CPx showed that there were hemorrhagic foci in the myocardium, deterioration and hyalinization in the myocardial fibers [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While pleomorphic nuclei (indicated by the yellow arrow) and focal necrosis (indicated by the black arrow) are observed in the heart muscle of the rats administered CPx + 5 mg/kg kefir (Figure 8d), a focal hyalinization area (indicated by the gray arrow) is observed in the heart muscle of the rats administered CPx + 10 mg/kg kefir (Figure 8f). Also, studies have shown that in the cardiac tissue of experimental groups given CPx, there are changes in the staining properties of the cell cytoplasm, a darker color and shrinkage in the nuclei, bleeding between muscle cells, small inflammatory cell foci and the separation of muscle fibers [12,25]. The histological findings of the experimental study conducted by Motawi et al (2010) involving the administration of 200 mg/kg CPx showed that there were hemorrhagic foci in the myocardium, deterioration and hyalinization in the myocardial fibers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that CPx induction causes hepatoxicity by increasing ALT, AST, ALP and LDH levels [ 21 , 22 ]. In many other studies, it has been reported that CPx applications at various doses increase enzymes such as AST, ALT, ALP, CK and LDH and cause histopathological changes [ 23 , 24 , 25 ]. Some antioxidative agents are used to suppress the high-dose effects of antineoplastic drugs and reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. According to Singh (1988), as referenced by Avci et al (2016) and Collins (2004) as referenced by Avci et al (2016) No OECD…”
Section: Bacterial Reverse Mutation Studiesmentioning
confidence: 99%
“…signif. increase of DNA damageCurcumin does not induce DNA damage and reduced damage by CP Negative DNA fragmentation in liver and kidney cells (ELISA): not increased by curcuminAccording to Singh (1988), as referenced by Avci et al () and Collins (2004) as referenced by Avci et al ()No OECD Reliable with restrictions Only one dose testedHighest dose tested below OECD recommendationsHistorical data not provided Low Çelik et al., BM cells of Swiss albino rats (Wistar rats), 6–8 week oldFemales (9 groups of 6 rats) curcumin treated group; 3 PFOS treated groups, 3 PFOS + Curcumin treated groupsNegative and positive controlsAim of the study:modulation on effects induced by perfluorooctane sulfonate (PFOS)Curcumin (Sigma Aldrich, purity > 94%) Relevance: high Vehicle: salinePositive control: MMC (2 mg/kg i.p. )Curcumin 80 mg/kg bw by gavage for 30 days at 48 h intervals, sacrificed 30 h after last treatmentCo‐administered with PFOS (0.6, 1.25 and 2.5 mg/kg bw)100 comet images scored per treatment; visually by two scorers, intensity for 0 (undamaged) to 4 (high damage)C+: stat.…”
Section: Appendix a – Summary Of The Available In Vitro And In Vivo Gmentioning
confidence: 99%
“…The use of this plant in liver disease and the gastrointestinal problem describes in ancient medical books [9] . In folk medicine, in many countries, S. marianum (L.) is used for the treatment of gallbladder and liver disorders (jaundice, cirrhosis, and hepatitis) [10] and protection against environmental and chemical liver poisoning [11] . Silymarin is widely used as a nutritional supplement or therapeutic agent in liver disease without serious side-effects in both animals and humans [12,13] .…”
Section: Introductionmentioning
confidence: 99%